The emerging role of the fibroblast growth factor-23–klotho axis in renal regulation of phosphate homeostasis - Razzaque, Mohammed S (2007)
Normal mineral ion homeostasis is tightly controlled by numerous endocrine factors that coordinately exert effects on intestine, kidney, and bone to maintain physiological balance. The importance of the fibroblast growth factor (FGF)-23–klotho axis in regulating mineral ion homeostasis has been proposed from recent research observations. Experimental studies suggest that 1) FGF23 is an important in vivo regulator of phosphate homeostasis, 2) FGF23 acts as a counter regulatory hormone to modulate the renal 1α-hydroxylase and sodium–phosphate cotransporter activities, 3) there is a trend of interrelationship between FGF23 and parathyroid hormone activities, 4) most of the FGF23 functions are conducted through the activation of FGF receptors, and 5) such receptor activation needs klotho, as a cofactor to generate downstream signaling events. These observations clearly suggest the emerging roles of the FGF23–klotho axis in maintaining mineral ion homeostasis. In this brief article, we will summarize how the FGF23–klotho axis might coordinately regulate normal mineral ion homeostasis, and how their abnormal regulation could severely disrupt such homeostasis to induce disease pathology.